From Leader-Driven Action to Collective Learning: An Adaptive Community Empowerment Model in Circular Waste Economy (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze how community empowerment develops within a waste-based circular livelihood model in a low-capacity context, with particular attention to the role of adaptive leadership as a transitional mechanism toward participatory autonomy. Method: The research employed a qualitative Participatory Action Research (PAR) design conducted at Padepokan Siloka SMART, a tempe-producing community facing environmental challenges due to unmanaged soybean pulp waste. Data were collected through semi-structured interviews, participatory observation, focus group discussions, and documentation. The data were analyzed using thematic analysis involving open, axial, and selective coding to identify patterns in leadership dynamics, livelihood adaptation, and experiential learning processes. Results: The findings indicate that empowerment did not initially emerge from spontaneous participation but from leader-driven initiation due to limited reflective capacity and economic vulnerability among predominantly elderly members. Adaptive leadership functioned as a catalytic and pedagogical mechanism that scaffolded collective action. The integration of long-term livestock investment with short-cycle sorghum cultivation stabilized participation, reduced environmental pollution, diversified income sources, and strengthened social capital. Novelty: This study proposes an adaptive transitional empowerment model that reconceptualizes leadership as a staged learning mechanism rather than a contradiction to participation, contributing to recent educational research on experiential and context-sensitive community transformation.